Xiaoyaosan Exerts Antidepressant Effect by Downregulating RAGE Expression in Cingulate Gyrus of Depressive-Like Mice - Weixin Yan; Weixin Yan; Zhaoyang Dong; Di Zhao; Jun Li; Ting Zeng; Chan Mo; Lei Gao; Lei Gao; Zhiping Lv (Frontiers Media S.A., 2021)
Xiaoyaosan (XYS), as a classic Chinese medicine compound, has been proven to have antidepressant effect in many studies, but its mechanism has not been clarified. In our previous studies, we found that chronic stress can induce depressive-like behavior and lead to emotion-related cingulate gyrus (Cg) dysfunction, as well as the decrease of neurotrophic factors and the increase of inflammatory-related proteins. Therefore, we speculated that XYS may play an antidepressant role by regulating the inflammation-related receptor of advanced glycation protein end product (RAGE) to affect the functional connectivity (FC) signal of the Cg and improve the depressive-like behavior. In order to verify this hypothesis, we analyzed the FC and RAGE expression in the Cg of depressive-like mice induced by chronic unpredictable mild stress (CUMS) and verified it with RAGE knockout mice. At the same time, we detected the effect of XYS on the depressive-like behavior, expression of RAGE, and the FC of the Cg of mice. The results showed that the FC of the Cg of depressive-like mice induced by CUMS was weakened, and the expression of RAGE was upregulated. The antidepressant effect of XYS is similar to that of fluoxetine hydrochloride, which can significantly reduce the depressive-like behavior of mice and inhibit the expression of the RAGE protein and mRNA in the Cg, and increase the FC of the Cg in mice. In conclusion, XYS may play an antidepressant role by downregulating the expression of RAGE in the Cg of depressive-like mice induced by CUMS, thereby affecting the functional signal and improving the depressive-like behavior.